Immunohistochemistry and Bioinformatics Identify GPX8 as a Potential Prognostic Biomarker and Target in Human Gastric Cancer - Zhang, Xiaojie; Xu, Heng; Zhang, Yunan; Sun, Chongyuan; Li, Zefeng; Hu, Chunfang; Zhao, Dongbing; Guo, Chunguang (Frontiers in Oncology, 2022)
Background: Glutathione peroxidase 8 (GPX8) is a type II trans-membrane protein with rare structural features belonging to the glutathione peroxidase family. The function of GPX8 in stomach adenocarcinoma has not been discovered clearly. Methods：In this study, we comprehensively analyzed the expression of GPX8 in stomach adenocarcinoma and discovered it is a potential target in the treatment of stomach adenocarcinoma. Immunohistochemical staining of GPX8 and survival analysis were performed in carcinoma tissue and adjacent tissues of 83 gastric cancer patients. Result: Based on GEPIA and TCGA database, mRNA expression of GPX8 was significantly higher in stomach adenocarcinoma compared with the adjacent normal tissues. GEPIA and Kaplan-Meier plotter databases showed higher GPX8 expression level was correlated with poor prognosis survival of stomach adenocarcinoma suggesting that GPX8 was a risk factor of poor prognosis survival in stomach adenocarcinoma. TIMER database showed GPX8 expression level was positively correlated with infiltrating levels of CD8+ T cells, CD4+ T cells, macrophages, neutrophils and dendritic cells in stomach adenocarcinoma. GSEA database indicated GPX8 was positively correlated with B cells, dendritic cells, CD4+ T cells, CD8+ T cells, macrophages, mast cells, monocytes, natural killer cells. At last, GO analysis indicated the biological processes were enriched in collagen fibril organization, endodermal cell differentiation, collagen metabolic process, extracellular matrix organization, etc. KEGG signaling pathway analysis showed GPX8 was correlated with protein digestion and absorption, extracellular matrix receptor interaction, AGE/RAGE signaling pathway, etc. GSEA database showed that GPX8 was positively associated with the angiogenesis, epithelial mesenchymal transition, hedgehog signaling, etc. The immunohistochemical staining of GPX8 and survival analysis in 83 gastric cancer patients showed the OS rate of patients with high GPX8 expression was significantly lower than the low GPX8 expression group. Conclusion: GPX8 was an important factor which might be a potential target in the treatment of stomach adenocarcinoma.